ILLUSTRATE THE LEARNED MAN, TRAIN THE MILITANT. AN ANALYSIS OF THE EL PEQUEÑO LIBRO SOCIALISTA COLLECTION, 1933-1949 - Martínez Mazzola, Ricardo (Universidad Nacional del Litoral, 2018)
This article studies the collection El Pequeño Libro Socialista (EPLS), the most systematic series of books and brochures published by the Partido Socialista in the 1930 and 1940s. It traces a history of EPLS, organizing a periodization that relates the changes in the collection with the transformations of political conjuncture, with the different strategies of the PS, and with the material conditions in which the editions were made. The place of the collection is reconstructed within the publications of the PS, which allows us to advance in the definition of some features of their editorial policy. EPLS was not limited to the function of dissemination to the general public but, increasingly, to form socialist militancy.